Diagnostic applications of the "pattern" electroretinography and visual evoked potentials in the evaluation of disorders of visual pathway function in Parkinson's disease - Stamenović, Jelena; Živadinović, Biljana; Djurić, Vanja; Ljubisavljević, Srdjan (Vojnosanitetski pregled, 2022)
ABSTRACTBackground and Aim: In spite of continuous research efforts, specific laboratory, neuropsychological or neurophysiological tests for the diagnosis of Parkinson’s disease have not been established. The aims of the paper are to determine the impact of visual pathway disorders on “pattern” electroretinogram and visual evoked potentials in certain stages of Parkinson's disease.Materials and Methods: The study was carried out in a group of 60 persons of both sexes, who were suffering from idiopathic Parkinson's disease at the I-IV stage of the desease according to the Hoehn and Yahr scale, and 30 healthy persons in the control group. The battery of non-invasive neurophysiological tests was used to estimate the functional status of the visual pathway: "pattern" electroretinography (PERG) and visual evoked potentials (VEP).Results: In the early phase of PB there is a linear increase in the latency of the wave N50 of the "pattern" electroretinogram and the wave P100 of the visual evoked potentials with significant extension of the latency of the N50 and P100 waves in subsequent stages of Parkinson's disease. Diagnostic application of the "pattern" electroretinography and visual evoked potentials enables the confirmation of a disorder in the visual pathway function in Parkinson's disease.Conclusion: These neurophysiological techniques may record early changes in the function of retinal structures and the optic nerve in PD, which might be significant both from the diagnostic and therapeutic aspects.
Keywords: diagnosis; electroretinography; evoked potentials, visual; parkinson’s disease.